2018
DOI: 10.3390/sports6030065
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Women’s Basketball: A Comparison among Continental Championships

Abstract: The aims of this study were (i) to compare basketball game-related statistics in women by region (Africa, America, Asia, Europe), and (ii) to identify characteristics that discriminate performances for each region. A total of 134 games from each continental championship held in 2017 were analyzed. A one-way ANOVA followed by a Bonferroni-adjusted pairwise comparison was performed to evaluate differences in each variable between the continents. A discriminant analysis was performed to identify game-related stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 23 publications
(43 reference statements)
4
22
1
Order By: Relevance
“…KPIs need to be especially emphasized in our study, TOV and STL. Our study found that African players from all of positions made more TOV compared with the corresponding positional players from other continental championships which was linked to the studies of Sampaio et al [ 3 ] and Madarame [ 8 ] suggested that the game pace and the unorganized manner of play in Africa were the main reasons that lead to the emergence of turnovers. In addition, it is worth noting that European guards had the lowest number of steals and the differences were clear in the pairwise comparison.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…KPIs need to be especially emphasized in our study, TOV and STL. Our study found that African players from all of positions made more TOV compared with the corresponding positional players from other continental championships which was linked to the studies of Sampaio et al [ 3 ] and Madarame [ 8 ] suggested that the game pace and the unorganized manner of play in Africa were the main reasons that lead to the emergence of turnovers. In addition, it is worth noting that European guards had the lowest number of steals and the differences were clear in the pairwise comparison.…”
Section: Discussionsupporting
confidence: 82%
“…Our results showed that European guards performed less 3 ptA than Asian guards whereas they committed more PF than Asian guards, which were linked with the previous studies suggested that European guards tend to be more cautious before shooting three points, especially in a lower ball possession because the competition level in Europe maintains a higher game intensity [ 7 , 8 ]. In addition, Sampaio and Janeira [ 27 ] suggested that fouls were an effective way to ball possession recovery.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is corroborated by the fact that a mere 15 months after the first experimental basketball match was played between two classes at Springfield YMCA (21 December 1891), Senda Berenson Abbott organized the first ever match between women's teams in this sport at Smith College, Northampton, Massachusetts, on 22 March 1893 (Simović and Pavlović, 2013). It must be said, though, that in the past decade the trend has been shifting and numerous papers have been published on this topic (Bazanov and Rannama, 2015;Conte and Lukonaitiene, 2018;Dimitros et al, 2013;Fylaktakidou et al, , 2013Koon et al, 2011;Kreivyte et al, 2013;Leicht et al 2017;Madarame 2018aMadarame , 2018bMadarame , 2018cMadarame , 2018dMilanović et al, 2016;Moreno et al 2013;Șentuna et al, 2018;Simović et al, 2017;Veleirinho and Tavares, 2013).…”
Section: Introductionmentioning
confidence: 99%